Foucault in Sulawesi: Challenging the Roots of Ethnic Discourse in South Sulawesi - Muh Adnan Malewa (IAFOR Journal of Cultural Studies)
The conflict between the Bugis and Makassar ethnic groups in South Sulawesi can be described as a silent conflict that could become the catalyst for the birth of a bigger war. To this day, this silent war continues through hate speech created from collective memory and even summarized in national historical writings. This cannot be separated from the local history of the 17th century, which did not yet have the idea of Indonesia as a united nation at its root. This idea only appeared as a manufactured development in the 20th century and was inscribed into the previous time period retroactively, creating a false national historical continuity. This was the state of things when in 1973 Sultan Hassanuddin (1631-1670), a representative of the Makassar ethnic group and someone who did not contemplate the idea of a unified Indonesia, was named a national hero with support from historians. He was viewed as a national hero because of his struggle against the Vereenigde Oostindische Compagnie (VOC), and then automatically labeled his opponent, Arung Palakka, a member of the Bugis ethnic group, as a “traitor” for joining the VOC. To this day, this interpretation is Indonesia’s dominant historical narrative and is often portrayed as a singular and absolute fact. This article attempts to answer how this metanarrative was formed by reviewing and questioning the narrative of the birth of ethnicity in South Sulawesi and by revisiting the two narratives of the great war between what ethnographers call the Bugis and the Makassar. In searching for the roots of this conflict, the researcher used a historical research methodology by interacting with various historical archives and research results heuristically, which were then deconstructed according to a metanarrative of source criticism in order to analyze the chronology of the birth of the ethnic identity of the people of South Sulawesi. Additionally, the 1609-1669 conflict is addressed, using Michel Foucault’s theory of power relations and knowledge. This research discovered how ethnic polarization occurred and offers possible corrections and additions to previous historians’ historical interpretations based more on national interests than historic facts. It is hoped that through this article, cultural historians can better review and separate historical facts from national interests that emerged in dominant historical writings, and might even help to reduce possible ethnic unease which might have occurred as a result.